PEMANFAATAN TAHU SUMEDANG PADA PRODUK SWEDISH MEATBALLS - Surya Nurhadi; Riza Taufiq (LPSDI Bina Patria, 2024)
Swedish meatballs are one of the iconic dishes at one of the IKEA shopping centers. Swedish meatballs are rich in healthy nutritional content. However, there are still a few who use the basic ingredient Sumedang tofu as a food product that is easy to innovate into new products. Researchers took the basic ingredients of Sumedang tofu based on interests and also new creations that had never been developed before. The author intends to research the use of sumedang tofu in Swedish meatballs. The method used is an experimental method, namely by substituting the additional main ingredient of tofu into Swedish meatball. The tests carried out are organoleptic tests and consumer acceptance of the product results. The main objective of this research is to obtain the right recipe formulation and to determine consumer acceptance by distributing questionnaires to 70 panelists. The results of this research obtained the correct recipe formula by adding 250 grams of Sumedang tofu to the Swedish meatball dough. based on the results of organoleptic tests obtained positive consumer acceptance of the processed product.